Young-onset dementia: scoping review of key pointers to diagnostic accuracy. Issue 3 (May 2019) - O'Malley, Mary; Parkes, Jacqueline; Stamou, Vasileios; LaFontaine, Jenny; Oyebode, Jan; Carter, Janet
Abstract : Background: Routine psychiatric assessments tailored to older patients are often insufficient to identify the complexity of presentation in younger patients with dementia. Significant overlap between psychiatric disorders and neurodegenerative disease means that high rates of prior incorrect psychiatric diagnosis are common. Long delays to diagnosis, misdiagnosis and lack of knowledge from professionals are key concerns. No specific practice guidelines exist for diagnosis of young-onset dementia (YOD). Aims: The review evaluates the current evidence about best practice in diagnosis to guide thorough assessment of the complex presentations of YOD with a view to upskilling professionals in the field. Method: A comprehensive search of the literature adopting a scoping review methodology was conducted regarding essential elements of diagnosis in YOD, over and above those in current diagnostic criteria for disease subtypes. This methodology was chosen because research in this area is sparse and not amenable to a traditional systematic review. Results: The quality of evidence identified is variable with the majority provided from expert opinion and evidence is lacking on some topics. Evidence appears weighted towards diagnosis in frontotemporal dementia and its subtypes and young-onset Alzheimer's disease. Conclusions: The literature demonstrates that a clinically rigorous and systematic approach is necessary in order to avoid mis- or underdiagnosis for younger people. The advent of new disease-modifying treatments necessitates clinicians in the field to improve knowledge of new imaging techniques and genetics, with the goal of improving training and practice, and highlights the need for quality indicators and alignment of diagnostic procedures across clinical settings. Declaration of interest: None.